A NEW SPECIES OF SIGMOIDOTROPIS (PAPILIONOIDEAE, LEGUMINOSAE) FROM ATLANTIC FOREST, EASTERN BRAZIL - Santos, Felipe Da Silva; Ribeiro, Carolina Lima; Oliveira, José Florencio Cerqueira; Soares, Kleber De Araújo; Queiroz, Luciano Paganucci De (Phytotaxa, 2024)
The Brazilian Atlantic Forest is one of the world’s most biodiverse regions and a key center of endemism for various plant groups. Here, we propose the new species Sigmoidotropis snakiae, which is found in the high-altitude Atlantic Forests of southeastern Brazil. Environmental niche modeling indicates potential areas of distribution that are distinct from the known range of the species, suggesting that these current areas may be remnants of a once-larger, interconnected habitat. The significance of conservation areas such as Parque Nacional do Caparaó and Parque Estadual do Forno Grande for the preservation of this species is emphasized. Sigmoidotropis snakiae, together with S. grandiflora, is only the second species of the genus identified in the Brazilian Atlantic Forest.